Microscopic Characteristics Of Scalp Hair Subjected To Cultural Styling Methods In Ghanaian African Females - Essel EA; Ahenkorah J; Blay RM; Adjenti SK; Adutwum-Ofosu KK; Hottor BA; Addai FK (Dove Medical Press, 2019)
Esther Adjoa Essel, John Ahenkorah, Richard Michael Blay, Saviour Kweku Adjenti, Kevin Kofi Adutwum-Ofosu, Bismarck Afedo Hottor, Frederick Kwaku Addai Department of Anatomy, School of Biomedical & Allied Sciences, College of Health Sciences, University of Ghana, Accra, GhanaCorrespondence: Frederick Kwaku AddaiDepartment of Anatomy, School of Biomedical & Allied Sciences, College of Health Sciences, University of Ghana, P. O. Box KB 143, Korle-Bu Campus, Accra, GhanaTel +233244643209Email addaifrederick88@gmail.comPurpose: To provide data for forensic use and provoke ideas to preserve shaft integrity, we studied microstructural alterations of female scalp hair subjected to Ghanaian cultural styling methods. Hence, topographical features of female hairs styled by braiding/weaving, and chemical relaxation sampled from five different scalp regions were assessed and compared with natural (Afro) hair.Subjects and methods: Ninety-six indigenous Ghanaian females volunteered 480 hairs, which were analyzed by light microscopy. Hairs were plucked using a pair of cosmetologist’s tweezers from frontal, left temporal, right temporal, vertex, and occipital regions of the scalp. Hairs were categorized by their grooming styles as Afro (natural-unstyled), natural-styled (weaved/braided), and chemically relaxed. These were studied according to shaft/medulla dimensions and conventional cuticular scale features, and comparisons were made between styling procedures and scalp regions.Results: Chemically styled hair had the widest shaft diameter, but the lowest incidence of continuous medullation. Medullary diameter and index increased from chemically relaxed, natural-styled, to Afro hair. A positive but modest correlation between shaft and medullary diameters existed for Afro (r = 0.320, p = 0.011) and natural-styled hairs (r = 0.235, p = 0.022) but not chemically relaxed hair (r = 0.122, p = 0.2). Scale margins were predominantly smooth in Afro hair, crenate in natural-styled hair, and rippled in chemically relaxed hair. With respect to scalp regions, hair shaft diameter was widest in vertex hair and smallest in right temporal hair in all styling methods.Conclusion: Medulla was thickest in Afro hair, which also exhibited a correlation with shaft diameter in conformity with the published data. Chemically relaxed hairs did not exhibit these characteristics, which affirm altered morphology. Research on how chemicals affect these changes should help find antidote. The dimensional variations of hairs from different scalp regions are instructive for both cosmetic and forensic examination of hairs.Keywords: skin appendage, integument, strand grooming, fiber scales, Afro hair